Improving social skills in care management provided by nurses: intervention research - Juliana Helena Montezeli; Maria do Carmo Fernandez Lourenço Haddad; Mara Lúcia Garanhani; Aida Maris Peres
ABSTRACT Objective: to analyze the process of introducing an educational intervention for the improvement of social skills in care management provided by nurses. Method: intervention research, according to its complexity, carried out in a South-Brazilian public university hospital. To identify learning needs, 11 nurses were interviewed and educational meetings were held with 20 participants, who evaluated with open-ended questions: what they would stop doing; what they would continue doing; and what they would start doing on the issues addressed. The data was analyzed comprehensively. Results: we developed 30 educational hours on social skills of communication, work, assertiveness, and other themes inherent in care management mentioned by the participants as deficient. The evaluation revealed intentions of advances in: self-monitoring, communication, empathy, assertiveness, leadership and search for knowledge. Monthly meetings on care management were formally requested by the institution. Final considerations: social skills are intertwined in care management relationships and their improvement has proved to be dialogical, recursive and hologrammatic.